(untitled) (Bulletin KNOB, 1996)
Work and personality of P.J.H. Cuypers (1827-1921), the leading representative of gothic rationalism in the Netherlands, have been given a central role in the history of modern Dutch Architecture. This article shows that this position has only in part to do with his actual role in Dutch architectural history and is most of all a result of the rewriting of this history from a progressive, avant-gardist point of view. Until the end of the nineteenth century Cuypers’ gothic rationalism was seen as one of the exponents in the continuing search for a new style. In the late eighties and early nineties however, a young generation of rationalists, all members of Architectura et Amicitia, an Amsterdam based architectural society, ’discovered’ him as both their theoretic and artistic forefather in the avant-garde. By making him into the only relevant architect emerging from the confusion of styles in the second half of the nineteenth century, they could position their own rationalism - based, as was Cuypers’, on the theories of Viollet Ie Duc - as the leading avant-garde architecture of their times. In a series of articles and special issues of the periodical Architectura, all commemorating special occasions in Cuypers’ life and career, they introduced the topos of the Rijksmuseum in Amsterdam as breaking point in Dutch architectural history. This building marked the supposed reawakening of progressive architecture, after a long period of uninspired classicism. It also marked the breakthrough of a Dutch arts and crafts movement, which had been created singlehandedly by Cuypers from his workshop in Roermond - a Red House avant-la-lettre. Cuypers problematic conservative ideology and his - in the eyes of the avant-garde - outdated position on historic ornament where effectively separated from his progressive architectural theory and design method by putting him forward as an above all admirable ’caracter in architecture’. Not his work, but his artistic attitude was to be considered a lasting example. With his Bauhausbuch ’Hollandische Architektur’ J.J.P. Oud canonised this view of the birth of modernism in the Netherlands and made it internationally accepted - to a certain extend till today.